CELEBRATING WOMANISM THROUGH INTERTEXTUALITY IN SAPPHIRE’S PUSH AND ALICE WALKER’S THE COLOR PURPLE - Rahajeng Hauwwa Khissoga (ELLITE, 2020)
The objects of this study are Alice Walker’s The Color Purple and Sapphire’s Push. This study is trying to unveil the interxtuality between the two works of literature above in order to trace back Sapphire’s attempt of celebrating Womanism in Black American women literature through intertextuality. This study focuses on how Alice Walker’s idea of Womanism in The Color Purple influences Sapphire to write a novel with a similar topic of discussion under the umbrella of Womanism. Womanism  is quite essential to the Black American women empowerment. Womanism can be seen as a weapon for the black women to fight back the partriarchal society. Supported by citations and quotations in both novel, this study tries to uncover how similar these novel are when working on the isssue of Womanism undergone by Black American women. Both Sapphire and Walker highlight the value of literacy and/or education for the Black American women as a way out of the repressive and dominating society. They both also concern about Black women supporting other Black women in both of the novels. Living in an unfortunate world where they were placed them at the bottom of social ladder, both of the main characters of the novel need the support from other Black Women in order to survive. The similarity of the theme of the novels and also several mentions of Alice Walker’s work of literature in Push manifested the Sapphire’s celebration of womanism through interxtuality in her novel.